Corneal Myofibroblast Generation From Bone Marrow-derived Cells - Barbosa, Flavia L. (2010)
The purpose of this study was to determine whether bone marrow-derived cells can differentiate into myofibroblasts, as defined by alpha smooth muscle actin (SMA) expression, that arise in the corneal stroma after irregular phototherapeutic keratectomy and whose presence within the cornea is associated with corneal stromal haze. C57BL/6J-GFP chimeric mice were generated through bone marrow transplantation from donor mice that expressed enhanced green fluorescent protein (GFP) in a high proportion of their bone marrow-derived cells. Twenty-four GFP chimeric mice underwent haze-generating corneal epithelial scrape followed by irregular phototherapeutic keratectomy (PTK) with an excimer laser in one eye. Mice were euthanized at 2 weeks or 4 weeks after PTK and the treated and control contralateral eyes were removed and cryo-preserved for sectioning for immunocytochemistry. Double immunocytochemistry for GFP and myofibroblast marker alpha smooth muscle actin (SMA) were performed and the number of SMA+GFP+, SMA+GFP−, SMA−GFP+ and SMA−GFP− cells, as well as the number of DAPI+ cell nuclei, per 400X field of stroma was determined in the central, mid-peripheral and peri-limbal cornea. In this mouse model, there were no SMA+ cells and only a few GFP+ cells detected in unwounded control corneas. No SMA+ cells were detected in the stroma at two weeks after irregular PTK, even though there were numerous GFP+ cells present. At 4 weeks after irregular PTK, all corneas developed mild to moderately severe corneal haze. In each of the three regions of the corneas examined, there were on average more than 9X more SMA+GFP+ than SMA+GFP− myofibroblasts. This difference was significant (p <0.01). There were significantly more (p <0.01) SMA−GFP+ cells, which likely include inflammatory cells, than SMA+GFP+ or SMA+GFP− cells, although SMA−GFP− cells represent the largest population of cells in the corneas. In this mouse model, the majority of myofibroblasts developed from bone marrow-derived cells. It is possible that all myofibroblasts in these animals developed from bone marrow-derived cells since mouse chimeras produced using this method had only 60% to 95% of bone marrow-derived cells that were GFP+ and it is not possible to achieve 100% chimerization. This model, therefore, cannot exclude the possibility of myofibroblasts also developed from keratocytes and/or corneal fibroblasts.